Iowa Birdline update, March 26, 1990 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1990)
Notes for the Iowa Birdline update for March 26, 1990. Highlights of the update include many reports from the height of waterfowl migration, one sighting in particular was comprised of 8000 waterfowl, including 4000 Ducks, 2000 Canada Geese, 1000 Snow Geese, and 1000 White-fronted Geese. Also of note were sightings of flocks of Smith's Longspurs, an early Common Loon, and an early Rough-winged Swallow. Epson - sheet feed/flatbed